2011
DOI: 10.3386/w17256
|View full text |Cite
|
Sign up to set email alerts
|

Wage Effects of Trade Reform with Endogenous Worker Mobility

Abstract: In this paper, we use a linked employer-employee database from Brazil to evaluate the wage effects of trade reform. With an aggregate (firm-level) analysis of this question, we find that a decline in trade protection is associated with an increase in average wages in exporting firms relative to domestic firms, consistent with earlier studies. However, using disaggregated, employer-employee level data, and allowing for the endogenous assignment of workers to firms due to match-specific productivity, we find tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 13 publications
1
45
0
1
Order By: Relevance
“…7 Differences in the workforce composition are also in line with the models of, for example, Helpman et al (2010), Davidson et al (2008) or Yeaple (2005). Krishna et al (2011) and Davidson et al (2010) have also found empirical evidence for matching effects and sorting. In a similar context, Krishna et al (2011) have shown, for Brazil, that the impact of trade openness on wages becomes insignificant if match effects are simultaneously considered.…”
Section: Matched Employer-employee Data For Germanymentioning
confidence: 60%
See 1 more Smart Citation
“…7 Differences in the workforce composition are also in line with the models of, for example, Helpman et al (2010), Davidson et al (2008) or Yeaple (2005). Krishna et al (2011) and Davidson et al (2010) have also found empirical evidence for matching effects and sorting. In a similar context, Krishna et al (2011) have shown, for Brazil, that the impact of trade openness on wages becomes insignificant if match effects are simultaneously considered.…”
Section: Matched Employer-employee Data For Germanymentioning
confidence: 60%
“…Krishna et al (2011) and Davidson et al (2010) have also found empirical evidence for matching effects and sorting. In a similar context, Krishna et al (2011) have shown, for Brazil, that the impact of trade openness on wages becomes insignificant if match effects are simultaneously considered. 8 Frias et al (2012) have presented evidence for the exporter wage premium using Mexican data.…”
Section: Matched Employer-employee Data For Germanymentioning
confidence: 91%
“…Overall, for Asia as well as the rest of the world, researchers find mixed results regarding this question. Helpman et al's (2017) and Krishna, Poole, and Senses's (2014) more recent work shows that wage inequality can have a non-monotonic or increasing relationship with respect to trade openness. Openness in trade leads to higher returns to exporting firms from investment in screening to find the best workers.…”
Section: Wage Inequalitymentioning
confidence: 99%
“…The most recent theoretical models of international trade (Olsen, 2006;Blinder, 2006;Grossman and Rossi-Hansberg, 2006;Helpman, 2011) reveal that the new patterns of trade, based on the international fragmentation of production and the international specialisation on the most efficient phases of the value chain rather than on the final output, give rise to gains in efficiency and welfare and, therefore, boost economic growth in the long term. However, there is also empirical evidence, based on both industry data (Amiti and Wei 2009;Winkler 2010;Michel and Rycx 2012;Agnese 2012;Cadarso, 2008, Bogliacino et al 2018 and business data (Görg and Hanley 2005;Hijzen et al 2015;Crinò, R. 2010;Liu and Trefler 2008;Martins and Opromolla 2009;Amiti and Davis 2011;Krishna 2011;Hummels et al, 2014) of the existence of short-term negative effects on employment and wages.…”
Section: Introductionmentioning
confidence: 99%